2022
DOI: 10.3389/fphar.2022.906468
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the mechanism behind and investigating the efficacy of Traditional Chinese Medicine and Traditional Tibetan Medicine in combination with standard therapeutics in hepatocellular carcinoma and cholangiocarcinoma in vitro

Abstract: In this study, we investigated compounds of plant and mushroom origin belonging to Traditional Chinese Medicine (TCM) and to Traditional Tibetan Medicine (TTM): a sandy beige mushroom Trametes robiniophila Murr, commonly known as Huaier/TCM as well as Ershiwuwei Songshi Wan and Qiwei Honghua Shusheng Wan, which both belong to TTM. We aimed to study the efficacy of TTM and TCM in hepatocellular carcinoma (HCC) and cholangiocarcinoma (CCA) in vitro. TCM and TTM were tested either as a monotherapy, or in combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…TTM has been employed to treat various types of cancer for centuries and is generally accepted across China and several other Asian countries [ 8 ]. It has been demonstrated that TTM drugs are efficacious against various types of cancers: they prevent inflammatory injuries and have comparatively weaker side effects [ 20 , 21 ]. As a conventional anti-inflammation and anticancer TTM drug, LWMX pills comprise six Tibetan herbal medications that have anti-CRC potential.…”
Section: Discussionmentioning
confidence: 99%
“…TTM has been employed to treat various types of cancer for centuries and is generally accepted across China and several other Asian countries [ 8 ]. It has been demonstrated that TTM drugs are efficacious against various types of cancers: they prevent inflammatory injuries and have comparatively weaker side effects [ 20 , 21 ]. As a conventional anti-inflammation and anticancer TTM drug, LWMX pills comprise six Tibetan herbal medications that have anti-CRC potential.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional Tibetan medicine (TTM) has a history of thousands of years, and many TTMs have been proven to have anticancer properties (6)(7)(8)(9)(10). Saffron is a traditional Tibetan medicine that has been reported to have anticancer effects in previous studies (11)(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%